The science of the soul in colonial New England - Rivett, Sarah; Omohundro Institute of Early American History & Culture (Chapel Hill : Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia, by the University of North Carolina Press, 2011)
Rivett challenges notions of Puritan provincialism as antithetical to the Enlightenment and demonstrates that, instead, empiricism and natural philosophy combined with Puritanism to transform the scope of the religious activity in colonial New England from the 1630s to the Great Awakening of the 1740s.
Evidence of grace -- Congregations : masculine form and reluctant women in puritan testimony -- Praying towns : conversion, empirical desire, and the Indian soul -- Death beads: tokenography and the science of dying well -- Witchcraft trials : the death of the devil and the specter of hypocrisy in 1692 -- Revivals : evangelical enlightenment -- Conversion in America.
Includes bibliographical references and index.
Print version record.
Keywords: Puritans; New England -- Church history -- 17th century; New England -- Church history -- 18th century; HISTORY -- United States -- Colonial Period (1600-1775); Puritans; New England; Empirie; Naturphilosophie; Puritaner; Neuengland; RELIGION / Christianity / Presbyterian; 1600 - 1799; Electronic books; Church history